Initial professional development for civil engineers - Waterhouse, Patrick (Civil engineer); Steels, H. Macdonald (ICE Publishing, 2018)
'Initial Professional Development for Civil Engineers' provides a core foundation of information on skills, knowledge and understanding, on which the development of every professional civil engineer, and their preparation for professional reviews, is based. The chapters provide guidance for any candidate and their mentors to make sense of the IPD process, providing a valuable insight into how to review their experience and the learning that they must take from it.